Genome-wide mapping of estrogen: receptor binding sites and activity - Carroll, Jason (Henry Stewart Talks, 2009)
Estrogen receptor-chromatin interactions, Cis-regulatory elements that function from a distance, ER binding sites and gene transcription, Co-operating transcription factors, Pioneer factors that maintain ER-chromatin interactions, Update interview: Consequence of transcription factors moving around genome, Update interview: Key proteins that are used during transcription, Update interview: What is impact of mutations in ER components, Update interview: Does ER complex cycle on the chromatin?, Update interview: Role of FOXA1 in mediating enhancer elements in cancer
Updated at 2020/09/18